Analysis of Organizational Factors on Patient Safety Culture at The Nganjuk General District Hospital - Djazuly Chalidyanto; Siti Fatonah; Mochammad Bagus Qomaruddin; Thinni Nurul Rochmah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
This study aimed to analyse the influence of organizational factors on patient safety culture at the Nganjuk General District Hospital. This was an analytical study with a cross-sectional design conducted from February 15 to March 14, 2020. Primary data were collected using a questionnaire distributed to 276 staff from 22 work units that provided direct services to patients. Secondary data were obtained from the profile and the Quality and Patient Safety Improvement Report of the Nganjuk General District Hospital in 2019. A cross-tabulation table was employed to analyze the influence of independent and dependent variables on patient safety culture with a percentage difference of less than 20%. The results showed that the majority of respondents were women (68.8%), had an associate degree III or equivalent education (57.6%), and had received training on patient safety (97.8%). The results of the cross-tabulation showed that organizational factors had an influence on patient safety culture at the Hospital. It is recommended that the Hospital pay attention to aspects that may affect patient safety culture since several work units still had a poor implementation of patient safety culture. Abstrak: Tujuan penelitian ini adalah menganalisis pengaruh faktor organisasi terhadap budaya keselamatan di Rumah Sakit Umum Daerah Nganjuk. Penelitian ini merupakan penelitian analitik dengan rancang bangun cross sectional pada 15 Februari sampai dengan 14 Maret 2020. Data primer dikumpulkan dengan panduan kuisioner pada 276 staf dari 22unit kerja yang memberikan pelayanan langsung kepada pasien.Data sekunder diperoleh dari profil RSUD Nganjuk dan laporan Komite PMKP RSUD Nganjuk tahun 2019. Analisis pengaruh menggunakan tabel tabulasi silang (cross tabulation) dengan selisih persentase kurang dari 20% antara variabel independen dan dependen.Hasil penelitian didapatkan bahwa mayoritas responden adalah perempuan (68,8%), memiliki pendidikan D3/sederajat (57,6%), dan telah mendapatkan pelatihan tentang keselamatan pasien (97,8%). Hasil tabulasi silang menunjukkan adanya pengaruh antara faktor organisasi terhadap budaya keselamatan pasien di RSUD Nganjuk.Disarankan RSUD Nganjuk kembali memperhatikan aspek-aspek yang dapat mempengaruhi budaya keselamatan pasien, mengingat masih terdapat beberapa unit kerja yang memiliki penilaian kurang terkait dengan aspek yang mempengaruhi budaya keselamatan pasien.